Cluster approach to regional oil and fat subcomplex development - N. R. Suchkova (Управление)
The article studies regional oil and fat subcomplex development in terms of the cluster approach application based on coordinating economic interests of sunflower seed producers, processing and marketing organizations under the condition of appropriate government support, as well as methodological, organizational, and information support by the relevant structures. On the basis of the production and economic indicators analysis it has been revealed that in the Saratov region sunflower production is quite effective, but the lack of interconnection between the oil and fat subcomplex subjects leads to uneven production volumes and highly varying profitability in the context of municipal districts of the region and lost profits formation at all stages of product movement. The author has developed a scheme of the regional oil and fat cluster subjects territorial location, represented by the areas of the cluster production core (with sunflower production volumes above the average regional level), production linking areas (with sunflower production volumes below the average regional level), as well as areas with developed infrastructure (with the presence of processing and storage facilities, and transportation hubs), allowing to establish an effective logistics system with mutually beneficial cooperation between regions. On the example of sunflower seed producers in the Saratov region clustering efficiency has been shown, which consists in production costs reduction as a result of transaction costs reduction and sales revenue growth due to the increase in the sunflower purchase price. The study results can be used in programs and proposals development to strengthen integration ties between the agro-industrial complex subjects.